Users behavioral intentions in adoption of AI-enabled robotic waiter services - Haque, A. K. M. Ahasanul; Maruf, Tarekol Islam; Akther, Naznin; Kabir, Sardar Md Humayun; Anis, Zohurul (Dalian University of Technology, 2025)
ABSTRACT This research investigates the determinants affecting the implementation of AI-powered robotic waiter services in Malaysian dining establishments. The study uses the Technology Acceptance Model (TAM) and the Service Robot Acceptance Model (sRAM) to combine practical factors (how useful and easy the service is), emotional factors (trust, how humanlike it seems, and safety), and relationship factors (perceived risk and attitude). A quantitative cross-sectional survey was executed among restaurant patrons in Klang Valley with a standardized questionnaire, yielding 300 responses. Researchers utilized Structural Equation Modelling (PLS-SEM) to determine the validity of the proposed correlations and mediation effects. The results demonstrate that perceived humanness, perceived safety, trust (through perceived simplicity of use), and attitude substantially affect the propensity to utilize robotic waiter services. Conversely, perceived risk exerts a detrimental influence. The findings demonstrate that emotional and relational variables are as crucial as functionality in promoting client acceptance of service robots within the hotel industry.